Tensions of Marriage: Love, Cooperation, Capitulation, Annihilation. - Frost, Velia (Clinical Social Work Journal, 2013)
This paper addresses the inevitable conflicts endemic to couple relationships. These conflicts are a manifestation of the mutual subjugation experienced by all couples engaged in an ongoing intimate relationship. The author describes this universal dimension of the life of a couple, applying what Ogden () calls 'the subjugating intersubjective third'-a third subject co-created through mutual projective identification, binding them together as a couple. The unconscious and conscious relationship between each partner and 'the third' generates a spectrum of primitive emotions from bliss to entrapment. Consequently, an identical situation in a relationship can evoke feelings of love and cooperation or capitulation and annihilation in one or both partners, depending on what is occurring in 'the third,' of which the members are both creators and captives. A clinical case illustrates this dynamic.